Effects of a national policy advocating rational drug use on decreases in outpatient antibiotic prescribing rates in Thailand - Onanong Waleekhachonloet; Thananan Rattanachotphanit; Chulaporn Limwattananon; Noppakun Thammatacharee; Supon Limwattananon (Centro de Investigaciones y Publicaciones Farmaceuticas, 2021)
Objective: This study examined the effects of a national policy advocating rational drug use (RDU), namely, the 'RDU Service Plan', starting in fiscal year 2017 and implemented by the Thai Ministry of Public Health (MOPH), on trends in antibiotic prescribing rates for outpatients. The policy was implemented subsequent to a voluntary campaign involving 136 hospitals, namely, the 'RDU Hospital Project', which was implemented during fiscal years 2014-2016. Methods: Hospital-level antibiotic prescribing rates in fiscal years 2014-2019 for respiratory infections, acute diarrhea, and fresh wounds were aggregated for two hospital groups using equally weighted averages: early adopters of RDU activities through the RDU Hospital Project and late adopters under the RDU Service Plan. Pre-/post-policy annual changes in the prescribing levels and trends were compared between the two groups using an interrupted time-series analysis. Results: In fiscal years 2014-2016, decreases in antibiotic prescribing rates for respiratory infections and acute diarrhea in both groups reflected a trend that existed before the RDU Service Plan was implemented. The immediate effect of the RDU Service Plan policy occurred in fiscal year 2017, when the prescribing level among the late adopters dropped abruptly for all three conditions with a greater magnitude than in the decrease among the early adopters, despite nonsignificant differences. The medium-term effect of the RDU Service Plan was identified through a further decreasing trend during fiscal years 2017-2019 for all conditions in both groups, except for acute diarrhea among the early adopters. Conclusions: The national policy on rational drug use effectively reduced antibiotic prescribing for common but questionable outpatient conditions.